2007
DOI: 10.1111/j.1365-3016.2007.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

The research implications of the selection of a gestational age estimation method

Abstract: There are three primary methods of gestational age estimation: dating based on last menstrual period (LMP), ultrasound-based dating and neonatal estimates. We review the strengths and limitations of each method as well as their implications for research. Dating based on LMP is a simple, low-cost method of estimating gestational age. Limitations associated with the use of menstrual-based dating include reporting problems such as uncertainty regarding the LMP date, possibly due to bleeding not associated with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
227
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(232 citation statements)
references
References 52 publications
3
227
0
2
Order By: Relevance
“…Although our study was limited by the uncertainties inherent in determining gestational age, the estimates used in our analyses are the same as those used by clinicians discussing potential outcomes of preterm infants with families. [17][18][19] Antenatal corticosteroid use is known to improve clinical outcomes in infants $26 weeks' gestation at birth. 20 In a recent analysis of NICHD NRN data, investigators observed a similar association between exposure to antenatal corticosteroid use among 22-to 25-week infants on the combined outcome of death or NDI (OR = 0.58 [95% CI: 0.42, 0.80]) 21 ; however, these results may be biased by the selective use of corticosteroids in pregnancies with other favorable prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was limited by the uncertainties inherent in determining gestational age, the estimates used in our analyses are the same as those used by clinicians discussing potential outcomes of preterm infants with families. [17][18][19] Antenatal corticosteroid use is known to improve clinical outcomes in infants $26 weeks' gestation at birth. 20 In a recent analysis of NICHD NRN data, investigators observed a similar association between exposure to antenatal corticosteroid use among 22-to 25-week infants on the combined outcome of death or NDI (OR = 0.58 [95% CI: 0.42, 0.80]) 21 ; however, these results may be biased by the selective use of corticosteroids in pregnancies with other favorable prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…IUGR diagnoses are calculated using 280 days to ideal foetal maturation and the onset of spontaneous labour (Saunders & Paterson, 1991), but other studies determined full maturation occurs at 279 days (Kieler, Axelsson, Nilsson, & Waldenstro, 1995), 281 days (Bersjø, Denman, Hoffman, & Meirik, 1990) and even 288 days (Mittendorf, Williams, Berkey, & Cotter, 1990). Each gestational day adds grams (Lynch & Zhang, 2007), so the day convention chosen in the machine is also a factor in predictive accuracy.…”
Section: Gestational Agementioning
confidence: 99%
“…A total of 513 pregnancies complied with our selection criteria and were scored. As estrus occurs 14 days before menstruation, and not in the middle of the menstrual cycle (due to delayed ovulation [13]), day 0 of fetal life was determined as 14 days before the next estimated menstruation. In case of a multiple pregnancy, the measurement of only 1 embryo was recorded.…”
Section: Methodsmentioning
confidence: 99%